A construção de espetáculos em teatro: o caso do grupo Os Satyros - Limeira, Tania Maria Vidigal (2011)
The objective of this thesis is to show how a theatrical play is created, considering the actors and director as the main creative agents. The object of study is the play Hipóteses para o amor e a verdade produced by the theatre group Os Satyros . In this perspective, theatre is considered a collective work, as a result of a broad range of knowledge and know-how of diverse people. The analysis reveals the several moments that constitute the theatre creation process, and especially the interrelationship between actors and director, focusing on the relations of interdependence, authority and autonomy